Rhoifolin Ameliorates Osteoarthritis via Regulating Autophagy - Yan, Jiyuan; Ni, Bowei; Sheng, Gaohong; Zhang, Yingchi; Xiao, Yifan; Ma, Yongzhuang; Li, Hao; Wu, Hua; Tu, Chang (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is a common age-related joint disease. Its development has been generally thought to be associated with inflammation and autophagy. Rhoifolin (Rho), a flavanone extracted from Rhus succedanea, has exhibited prominent anti-oxidative and anti-inflammatory properties in several diseases. However the exact role of Rho in OA remains unclear. Here, we investigated the therapeutic effects as well as the underlying mechanism of Rho on rat OA. Our results indicated that Rho could significantly alleviate the IL-1β-induced inflammatory responses, cartilage degradation and autophagy downregulation in rat chondrocytes. Moreover, administration of autophagy inhibitor 3-methyladenine (3-MA) could reverse the anti-inflammatory and anti-cartilage degradation effects of Rho. Furthermore, P38/JNK and PI3K/AKT/mTOR signal pathways were involved in the protective effects of Rho. In vivo, intra-articular injection of Rho could notably ameliorate the cartilage damage in rat OA model. In conclusion, our work elucidates that Rho ameliorated rat OA via regulating autophay, indicating the potential role of Rho in OA therapy.